2021
DOI: 10.1039/d1sm00100k
|View full text |Cite
|
Sign up to set email alerts
|

Topological defects of integer charge in cell monolayers

Abstract: Many cell types spontaneously order like nematic liquid crystals, and, as such, they form topological defects, which influence the cell organization. While defects with topological charge ±1/2 are common in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 46 publications
(79 reference statements)
1
37
0
Order By: Relevance
“…Similar inference of cell layer material properties based on theories of liquid crystals are also proposed by confining myoblasts in small circular adhesive islands to stabilise spiral topological defects at the centre of the confinement [81]. More recently, it is further shown that pre-patterned micron-sized ridges can be exploited to control alignment of fibroblast (3T6) and epithelial (EpH-4) cell layers to from stable full-integer topological defects [57]. Remarkably, it was shown that such pre-imposed patterns can control the activation/deactivation of mechanotransduction by triggering nuclear/cytoplasmic YAP translocation at topological defects with positive and negative charges and in different cell types.…”
Section: Exploiting Physics Of Liquid Crystals For Guiding Cellular S...mentioning
confidence: 54%
“…Similar inference of cell layer material properties based on theories of liquid crystals are also proposed by confining myoblasts in small circular adhesive islands to stabilise spiral topological defects at the centre of the confinement [81]. More recently, it is further shown that pre-patterned micron-sized ridges can be exploited to control alignment of fibroblast (3T6) and epithelial (EpH-4) cell layers to from stable full-integer topological defects [57]. Remarkably, it was shown that such pre-imposed patterns can control the activation/deactivation of mechanotransduction by triggering nuclear/cytoplasmic YAP translocation at topological defects with positive and negative charges and in different cell types.…”
Section: Exploiting Physics Of Liquid Crystals For Guiding Cellular S...mentioning
confidence: 54%
“…Defects are not purely mathematical tools and have important biophysical implications such as controlling cell death and extrusion from a tissue monolayer [33], localizing proliferation [34], and guiding collective density [35]. Thus the control of defects represents an attempt at harnessing the power of active matter to do work at the collective scale [36][37][38][39]. As we develop these technologies further, we can benefit from insights into new ways to shape and control these defects in a polarized active matter.…”
Section: Review On Defect Dynamics and Inverse Energy Cascadementioning
confidence: 99%
“…[18,19] New publications continue to cover a wide range of topological defects. These include active motion of topological defects in LC media, [20] decomposition of center and saddle point disclinations, [21,22] ionically charged comet orbit and saddle point disclinations in nematic LCs, [23] skyrmions, [24] motile solitons, [25] and vortex lattices. [26] One example of topological defects, in nematic LCs, is the occurrence of horizontal domains.…”
Section: Introductionmentioning
confidence: 99%